PUBLIC-PRIVATE PARTNERSHIP: ESSENCE, FUNCTIONS AND GLOBAL PRACTICE - A. Boldyrev (Вестник университета)
The author of the article explores the essence, functions and world experience of applying the mechanism of public-private partnership in the implementation of infrastructure projects. This article examines the practice of creating a regulatory framework, state associations and organizations whose purpose is to form and maintain stable links between public authorities and private businesses for the provision of public services. This article examines the experience of working with this mechanism in the territory of the countries of the European Union, the United States and the BRICS countries, and reveals the current trends in the development of public-private partnership in the modern world